Factors leading to noise-induced hearing loss among workers in spinning mills in Salem District, Tamil Nadu, India - Norman, Prasan; Karthikeyan, E.; Thirunaaukarasu , D.; Bavithra, J. (Orapuh Journal, 2023)
IntroductionHearing loss has become a common feature above 40 years of age. It is more common in Industrial workers who are constantly exposed to loud sounds. With the number of industries rising daily, noise-induced hearing loss has become a constant threat to industrial workers. Salem is one of the districts with lots of spinning mills. PurposeThis study was done to detect the factors leading to noise-induced hearing loss among workers in spinning mills in Salem District, Tamil Nadu, India.MethodsQuestionnaires containing questions on socio-demographic and work-related data were administered to 867 workers in spinning mills in Salem District. An Otolaryngologist screened their aural canal for wax, foreign bodies (which were removed if they persisted), and perforation in the tympanic membrane. Tuning fork tests and assessment of hearing by portable audiometry were done. The workplace’s noise level was measured with a mini sound level meter (model-METRAVI SL – 4010). Data analysis was done using the Statistical Package for Social Sciences (SPSS).ResultsThis study indicated that increased duration of work and Increased noise level in the workplaces, working more than ten years in a noisy environment, working more than 6 days a week, and working more than 8 hours a day were the factors associated with noise-induced hearing loss.ConclusionsNoise Induced hearing loss is very common in workers working in mills. Adopting the protective measures provided and having regular hearing assessments to prevent hearing loss is indicated.